Developing a taxonomy of medical errors and exploring the post-error recovery process: A QUAL → qual mixed-method design - Marie M. Prothero; Janice M. Morse (Elsevier, 2023)
In this project we used sequential qualitative, QUAL → qual (i.e., sequential qualitative mixed method-method design) to explore the experiences of 36 nurses involving 44 clinical errors. With the core QUAL component, we used content analysis to describe the context and develop a new taxonomy-Circumstances-of-Error. This compensates for limitations in the presently used scale, TERCAP, developed in 2002. The revised scale links error types with error causation, thus enabling the institution to identify problems within its system as well as personnel. Next, in the sequential qual component, we linked each type of error with the emotional impact experience by nurses involved in the process. A constructivist grounded theory with the post-error stages-Impact of the Error, Losing Competency and Reestablishing Competency-describes the emotional ramifications of the experience. Three types of responses were prevalent, somatic, angst, and mortification, which shattered the confidence of staff resulting in nurses leaving or transferring from the unit. In addition to the cost to patient safety, estimating the cost of errors must also include cost to professionals, staff in general, the institution, and to the profession.